Childhood stunting and associated factors among irrigation and non-irrigation user northwest, Ethiopia: a comparative cross-sectional study - Balew Sema; Muluken Azage; Mulat Tirfie (BMC, 2021)
Abstract Background Stunting is a critical public health problem of developing countries like Ethiopia. Different interventions like irrigation activity have been carried out by the government of Ethiopia to improve the nutritional status of the community. However, there is scanty of data on childhood stunting and its associated factors between irrigation user and non-irrigation user. Objective To assess the magnitude of childhood stunting and its associated factors between irrigation and non-irrigation user in North Mecha District, Northwest Ethiopia. Methods A community-based comparative cross-sectional study design was employed from October to November 2019. A systematic sampling was used to draw mothers with children age 6-59 months (582 irrigated and 582 non- irrigated household users). Data were collected using questionnaire and anthropometric measurement tools. Multivariable logistic regression was used to identify the predictors of stunting. Adjusted odds ratios with 95% CI were used to determine the degree of association between independent and outcome variable. A-p-value < 0.05 was used as cutoff point to declare statistically significant variables with the outcome variable. Results The prevalence of childhood stunting (6-59 months) among irrigation users [32.8% at 95%CI [29.1%-36.7%]] was slightly lower than non-users [40.2% at 95%CI [[36.3%-44.2%]]]. However, the difference did not show significant variation. The odds of childhood stunting were higher among a child from a mother had no antenatal visit, a child whose age was between 12 and 47 months, a child from a mother who did not use water and soap always for washing hands, and a child who had fever. Conclusion The prevalence of childhood stunting was high and did not show significant variation between irrigation and non-irrigation users. A child from mother had no antenatal visit, whose age was between 12 and 47 months, a mother who did not use water and soap always for washing hands, and who had fever were factors associated with higher child stunting. Thus, the identified modifiable factors should be strengthened to reduce stunting.